Effectiveness of Therapeutic Exercise in Musculoskeletal Risk Factors Related to Swimmer's Shoulder - Nuno Tavares; Gonçalo Dias; Paulo Carvalho; João Paulo Vilas-Boas; Maria António Castro (MDPI AG, 2022)
Background: Therapeutic exercise seems to minimize musculoskeletal risk factors related to swimmer's shoulder. However, there is an absence of a qualitative evaluation of these programs and a great variability regarding the characteristics of exercises. The objective of this review was to identify, evaluate, and compare exercise programs used to minimize musculoskeletal risk factors related to swimmer's shoulder. Methods: PubMed, CochraneLibrary, ScienceDirect, and Medscape were searched during January 2022. The research was limited to meta-analyses, systematic reviews, and RCTs written in English, Spanish, and Portuguese without publication time. The researched papers had swimmers as the population, compared an exercise program with another program or without intervention, and had as outcomes musculoskeletal risk factor variables. Results: Eleven articles were considered for analysis. There were three positive effects of strength programs on shoulder rotators' strength and endurance, two positive effects of strength and stretching programs on shoulder posture, and one positive effect of a stretching program on shoulder ROM and a plyometric program on proprioception. Conclusions: There is high heterogeneity and little methodological quality evidence about the theme. However, strength programs with five or fewer OKC exercises performed out of the water seems to lead to better results in the swimmer's shoulder prevention.